Tree Vitality and Forest Health: Can Tree-Ring Stable Isotopes Be Used as Indicators? - Paolo Cherubini; Giovanna Battipaglia; John L. Innes (Current Forestry Reports, 2021)
Purpose of Review Society is concerned about the long-term condition of the forests. Although a clear definition of forest health is still missing, to evaluate forest health, monitoring efforts in the past 40 years have concentrated on the assessment of tree vitality, trying to estimate tree photosynthesis rates and productivity. Used in monitoring forest decline in Central Europe since the 1980s, crown foliage transparency has been commonly believed to be the best indicator of tree condition in relation to air pollution, although annual variations appear more closely related to water stress. Although crown transparency is not a good indicator of tree photosynthesis rates, defoliation is still one of the most used indicators of tree vitality. Tree rings have been often used as indicators of past productivity. However, long-term tree growth trends are difficult to interpret because of sampling bias, and ring width patterns do not provide any information about tree physiological processes. Recent Findings In the past two decades, tree-ring stable isotopes have been used not only to reconstruct the impact of past climatic events, such as drought, but also in the study of forest decline induced by air pollution episodes, and other natural disturbances and environmental stress, such as pest outbreaks and wildfires. They have proven to be useful tools for understanding physiological processes and tree response to such stress factors. Summary Tree-ring stable isotopes integrate crown transpiration rates and photosynthesis rates and may enhance our understanding of tree vitality. They are promising indicators of tree vitality. We call for the use of tree-ring stable isotopes in future monitoring programmes.